Characterization of Cyanide in Gold Mine Tailings of the Witwatersrand, South Africa - Bakatula, EN; Tutu, H; Cukrowska, EM (Mine Closure 2008: Third International Seminar on Mine Closure, 2008)
Numerous old gold sand and slimes tailings dumps on the Witwatersrand have been reprocessed since the 1980s for residual gold extraction using cyanide as a lixiviant. There are numerous technologies available by which many cyanide species may be decomposed. However, at most gold mines in South Africa, cyanide is simply discharged with the effluent and tailings based on the assumption it will decompose within a relatively short period of time. However the distribution and fate of cyanide in the environment upon release from the tailings dumps depends on its physical-chemical speciation. This study describes the characterization of cyanide in the superficial deposits of a reprocessed gold tailings dump in the two years after slurry re-deposition by the cycloning method, and the implications for its potential release and redistribution during the hydraulic re-working and re-deposition of old tailing slurries. Sampling was done in 2006 and 2007 on a third-generation gold slimes dam to assess the impact of tailings acidification immediately after deposition on cyanide release over that period. The total concentrations of cyanide observed were higher than could be accounted for by the most recent processing event , and suggest that residual cyanide from the historical processing had persisted in the tailings since the original deposition (a period of 30 to 80 years, depending on the tailings facility). The re-working of the old slurries in the new facility resulted in a fairly rapid decline in pH of the superficial, drying, layer of the facility after deposition ceased. Elevated concentrations of total cyanide (CNT) and weak acid dissociable cyanide (CNWAD) were obtained for 2006. The concentrations of free cyanide (CNfree), cyanates (CNO -) and thiocyanates (SCN-) were higher for 2007 than 2006, and conversely the concentrations of metal-cyanide complexes, namely Cu(CN)3 2- (up to 35 mgkg-1), Fe(CN)6 4- (more than 80 mgkg-1) and Ni(CN)4 2- (up to 30 mgkg-1) were higher in 2006 compared to 2007. Decreases of 25% for Cu(CN)3 2-, >30% for Fe(CN)6 4-, and 40% for Ni(CN)4 2- were observed in some cases between the sampling periods. These findings indicate that metal cyanide species in the superficial layers of the tailings rapidly degraded post-deposition as a result, primarily, of a decrease in pH. The released cyanide is either volatilized as HCN, or transported in solution with the contamination plume.